Problematika Pengelolaan Pendidikan Islam : Dalam Diskursus Membangun Mutu Lulusan - Fadilatun Naimah; Musyarapah; Noorazmah Hidayati (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
The purpose of this article is to explain the problems of implementing management in Islamic educational institutions that are faced as challenges to improving the quality of education as well as constructive efforts to address them. The quality of graduates at Islamic educational institutions in general still needs to be improved. This is a problem that is currently still trying to find solutions and alternatives that can be used to improve the quality of these graduates. This research aims to determine the problems and implementation of quality standards for graduates of Islamic educational institutions. The method used in this article is a literature study by reviewing several literatures related to the theme that the author will study. The results show that one of the management problems in Islamic educational institutions is that there are still authoritarian and centralized leadership practices that apply in several Islamic educational institutions, and there is still a lack of quality human resources, especially in the academic field as well as inadequate facilities and infrastructure and lagging technology. Keywords: Islamic Education Institution; Problems of Islamic Education; Quality of graduates